2020
DOI: 10.1073/pnas.1913754117
|View full text |Cite
|
Sign up to set email alerts
|

Exploring histone loading on HIV DNA reveals a dynamic nucleosome positioning between unintegrated and integrated viral genome

Abstract: The aim of the present study was to understand the biology of unintegrated HIV-1 DNA and reveal the mechanisms involved in its transcriptional silencing. We found that histones are loaded on HIV-1 DNA after its nuclear import and before its integration in the host genome. Nucleosome positioning analysis along the unintegrated and integrated viral genomes revealed major differences in nucleosome density and position. Indeed, in addition to the well-known nucleosomes Nuc0, Nuc1, and Nuc2 loaded on integrated HIV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 65 publications
2
45
0
Order By: Relevance
“…More specifically, HIV-1 episomes have been found to be enriched in histone modifications typical of a repressive heterochromatin architecture, such as the trimethylation of histone 3 lysine 9 (H3K9me3) [ 42 ]. A recent report has confirmed this observation and shown that histones are loaded soon after the synthesis of HIV-1 DNA and before its integration in the host chromatin [ 43 ]. In particular, nucleosome positioning was found to dynamically vary at the 5′LTR between unintegrated and integrated forms of HIV-1 DNA [ 43 ].…”
Section: Epigenetic Mechanisms Of Hiv-1 Latencymentioning
confidence: 70%
See 2 more Smart Citations
“…More specifically, HIV-1 episomes have been found to be enriched in histone modifications typical of a repressive heterochromatin architecture, such as the trimethylation of histone 3 lysine 9 (H3K9me3) [ 42 ]. A recent report has confirmed this observation and shown that histones are loaded soon after the synthesis of HIV-1 DNA and before its integration in the host chromatin [ 43 ]. In particular, nucleosome positioning was found to dynamically vary at the 5′LTR between unintegrated and integrated forms of HIV-1 DNA [ 43 ].…”
Section: Epigenetic Mechanisms Of Hiv-1 Latencymentioning
confidence: 70%
“…A recent report has confirmed this observation and shown that histones are loaded soon after the synthesis of HIV-1 DNA and before its integration in the host chromatin [ 43 ]. In particular, nucleosome positioning was found to dynamically vary at the 5′LTR between unintegrated and integrated forms of HIV-1 DNA [ 43 ]. The more closed nucleosome lattice in the unintegrated viral promoter, in turn, prevented the transcription of viral genes [ 43 ].…”
Section: Epigenetic Mechanisms Of Hiv-1 Latencymentioning
confidence: 70%
See 1 more Smart Citation
“…For these reasons, it has been of interest to determine the properties of newly synthesized DNA formed by HIV-1 and compare them with those of the MLVs. Unintegrated HIV-1 DNAs formed by integration-defective virions, or formed in the presence of integrase inhibitors, were found to be heavily silenced, much like those of the MLVs [65][66][67]. Examination of the presence of histones on the unintegrated HIV-1 DNA by ChIP revealed the rapid loading of histones H3 and H2B, as seen for the MLVs [65,66].…”
Section: Silencing Of Unintegrated Hiv-1 Dnamentioning
confidence: 95%
“…Unintegrated HIV-1 DNAs formed by integration-defective virions, or formed in the presence of integrase inhibitors, were found to be heavily silenced, much like those of the MLVs [65][66][67]. Examination of the presence of histones on the unintegrated HIV-1 DNA by ChIP revealed the rapid loading of histones H3 and H2B, as seen for the MLVs [65,66]. Moreover, analysis of the histones by ChIP again revealed the presence of marks associated with silencing: histones bound to the HIV-1 viral DNA were heavily marked by H3K9me3, and were very low in H3 acetylation.…”
Section: Silencing Of Unintegrated Hiv-1 Dnamentioning
confidence: 99%